Does Financial Development Alleviate Poverty? Empirical Evidence from Indonesia - Wardana, Wahyu Wisnu; Diwanegara, Rosa; Prisandy, Rezza F.; Aminin; Rohim, Abdul (Universitas Airlangga, 2023)
This study examines the contribution of financial development to poverty reduction in Indonesia using the autoregressive distributed lag (ARDL) bound testing approach to the cointegration framework. It also employs annual data of several financial development measures such as domestic credit, broad money, and financial development indexes from 1986 to 2018. Our findings suggest that financial development and poverty reduction have a cointegration relationship, regardless of the financial development indicators used. Furthermore, we find that domestic credit, broad money, financial institution depth, financial market depth, financial market access, and financial market efficiency reduced poverty. It suggests that financial development reduced poverty through its indirect channel, i.e., the economic growth effect.